Formation of scientific foundations of digital communication in the construction industry: transformation of traditional product promotion models - Tormosov, R.; Hura, O.; Dubenskyi, O.; Hrohol, V. (Ways to Improve Construction Efficiency, 2024)
The digital transformation of the construction industry introduces new challenges and opportunities for organizing effective communication and product promotion. In the current context of increasing market digitalization, integration of information technologies, and the expansion of online platforms, there is a need to rethink traditional approaches to interaction with clients, partners, and stakeholders. Classical promotion methods, which relied on direct sales, advertising campaigns, and offline communication channels, are gradually losing their effectiveness due to the rapid expansion of social networks, analytical tools, and marketing automation systems. Analysis of digital communication technologies shows that the integration of CRM systems, ERP platforms, online marketing, social media, and Big Data analytics enables construction companies to significantly enhance the efficiency of interactions with their target audience. The methodological foundations for developing digital communication strategies include consumer segmentation, message personalization, integration of multi-level communication channels, and campaign performance evaluation through KPIs. The key principles for transforming traditional product promotion models include adaptability, flexibility, technology integration, and continuous updating of communication strategies in accordance with consumer behavior and market conditions. Particular attention is given to the formation of a digital communication infrastructure in the construction sector. The role of analytical platforms, performance monitoring tools, information exchange automation, and the creation of integrated digital ecosystems is considered, ensuring timely and accurate data transmission among all participants in the construction process. The socio-economic benefits of digital communication include increased operational transparency, reduced transaction costs, faster managerial decision-making, improved customer experience, and enhanced competitiveness of companies in the market. As a result, a comprehensive model of digital communication in the construction sector is proposed, integrating technologies, transforming traditional marketing approaches, and optimizing interactions with various stakeholder groups.